Size and Shape of Jupiter Trojan (2207) Antenor from Stellar Occultations - Ferreira, F. S.; Camargo, J. I. B.; Morgado, B. E.; Peixoto, V. F.; Desmars, J.; Braga-Ribas, F.; Gomes-Júnior, A. R.; Sicardy, B.; Ortiz, J. L.; Vieira-Martins, R.; Pereira, C. L.; Liberato, L. [UNESP]; et al. (American Astronomical Society, 2025)
Librating around the Lagrange L5, the Jupiter’s Trojan (2207) Antenor has been observed in recent years and its rotational light curve suggests it to be a very likely binary asteroid candidate. From stellar occultations, we report results from three events from Europe and North America to estimate the 2D apparent size and shape of Jupiter’s Trojan (2207) Antenor. For the best-fitted ellipse in the sky-plane, we determined that Antenor has a 2D apparent equatorial radius of 54.30 ± 0.99 km at the moment of the occultations, with an apparent oblateness of 0.144 ± 0.051. We highlight the positive detection from 2021 June 12, which shows an intriguing feature that can be interpreted as a very large topographical feature (of about 11 km) of the body or that can provide further evidence that this object is, in fact, a close or contact binary. We also determine astrometric positions, with uncertainties of a few milliarcseconds (mas) for our preferred solutions.